2017
DOI: 10.1590/s2175-97902017000115098
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of basil extract ( Ocimum basilicum L.) on oxidative, anti-genotoxic and anti-inflammatory effects in human leukocytes cell cultures exposed to challenging agents

Abstract: Ocimum is one of the most important genera of the Lamiaceae family. Several studies about basil and its popular use reveal many characteristics of the herb, including its use as antioxidant, anti-aging, antiinflammatory, anti-carcinogenic, anti-microbial, and cardiovascular agents, among others. In this paper, we evaluated genotoxic, oxidative, and anti-inflammatory parameters from the extract of Ocimum basilicum in different concentrations, using human leukocytes cultures exposed to challenging agents. Our re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 39 publications
3
42
0
4
Order By: Relevance
“…These entire compounds were reported to have a variety of biological activities (Table 3). This result is consistent with other studies reported that O. basilicum is rich in polyphenols like Phenolic acids 17,69 . It is interesting that the current study is not consistent with Murali and Prabakaran 27 whom found that O. basilicum methanol extract contains 13 compounds that did not resemble the chemical compounds found in this study.…”
Section: Discussionsupporting
confidence: 94%
“…These entire compounds were reported to have a variety of biological activities (Table 3). This result is consistent with other studies reported that O. basilicum is rich in polyphenols like Phenolic acids 17,69 . It is interesting that the current study is not consistent with Murali and Prabakaran 27 whom found that O. basilicum methanol extract contains 13 compounds that did not resemble the chemical compounds found in this study.…”
Section: Discussionsupporting
confidence: 94%
“…They used for cosmetic applications, fuel, medicine and food. Moreover, O. basilicum showed its potential for several biological activities, including antioxidant, anti-aging, anti-inflammatory, anticarcinogenic, anti-microbial, and cardiovascular agents, among others [15]. Additionally, O. basilicum seeds have been traditionally used as a natural remedy for the treatment of indigestion, ulcer, diarrhoea, sore throats, and kidney disorders [16].…”
Section: Introductionmentioning
confidence: 99%
“…Aburigal et al (2017)notified that DPPH values of different samples varied from 89.22% to 69.33%, with the highest antioxidant activity being in samples from Maldives, while the lowest antioxidant activity was found in samples from Thailand, and the antioxidant effectiveness is probably due to a relatively high content of methyleugenol in O. basilicum, in addition,the antioxidant activity of ethyl acetate extract was higher than ethanol extract. Güez et al (2017) confirmed that O. basilicum extract acts as an antioxidant and effectively overcomes the effects of high oxidizing agents such as hydrogen peroxide.…”
Section: Antioxidant Activitymentioning
confidence: 64%